Uma análise sobre as condições de realização do trabalho pedagógico dos professores de Educação Física na rede municipal de ensino da cidade de João Pessoa-PB - Macieira, Jeimison de Araújo (2010)
This study represents an effort to examine the conditions for achieving the educational work of physical education teachers in schools in the Municipality School of the City of João Pessoa - PB. Part of the analysis work, in general, and its expression in the working conditions of teachers of Physical Education. Therefore, we performed a survey of work category, as the basis of social being and its current configuration, reproduced in forms of employment as a result of the restructuring process, particularly outlining a way no less mindful of the precariousness of the effects of the pedagogical work of teachers Physical Education in the current political and economic moment. Aimed to carry out a survey on the conditions of realization of the pedagogic professor of Physical Education and its barriers in the organization of work processes. Moreover, we draw a parallel between the necessary work and education, particularly physical education, stimulating the search for the study of relevant issues related to the topic. From the data collected we were able to see, and to schools: most of them need to be transformed into its physical structure, as spaces remain in a precarious state of operation, where classes are held in sandboxes, dirt floors , disabled car parks, under trees, lateral areas and floors stone; about the course materials of instruction: materials such as balls, hoops, ribbons, strings and others in the great majority of schools is reduced in quantity, not meeting the needs students, as not enough to the scarcity of them still are - according to the directions and / or teachers - in bad or regular situation, thus contributing to the precariousness of the teacher's pedagogical work, and labor relations, established between teachers and City Hall, still maintain a contractual relationship where teachers service providers (called PS) do not have their contracts guaranteed the same rights as effective teachers. Also, given the data, we reaffirm our initial findings about the fact that physical education was being treated inside the school as a "party discipline", and used as a recreation outlet for the teachers of other subjects. We can see physical education as a discipline, decontextualized and isolated, unable to confront the contradictions within the classroom and school. Furthermore, the study enabled us to realize that there are possibilities for changing the teacher and pedagogical work that is necessary obsorver a method capable of revealing the essence of the social model to which we are subjected to, and guiding our prospects for change in the concrete level of social life that assimilate a learning approach to physical education that is in these theoretical frameworks and also able to think that gives another type of society, a society more just and equal.